2016
DOI: 10.1093/carcin/bgw075
|View full text |Cite
|
Sign up to set email alerts
|

Serum 5-LOX: a progressive protein marker for breast cancer and new approach for therapeutic target

Abstract: Lipoxygenase (LOX) pathway has emerged to have a role in carcinogenesis. There is an evidence that both 12-LOX and 5-LOX have procarcinogenic role. We have previously reported the elevated level of serum 12-LOX in breast cancer patients. This study evaluated the serum level of 5-LOX in breast cancer patients and its in vitro inhibition assessment with peptide inhibitor YWCS. The level of 5-LOX was determined by surface plasmon resonance (SPR). The peptide inhibitor of 5-LOX was designed by molecular modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
4
23
2
Order By: Relevance
“…However, the role of ALOX in breast cancer remains much unknown. This study firstly demonstrated that the ALOX5 expression elevated breast cancer tissues compared to control (Figures 1(a) and 1(b) ), which is supported by the report that the mean concentration of serum ALOX5 is significantly higher in breast cancer patients than similar age as the control group [ 17 ]. In addition, the serum level of ALOX5 among individual breast cancer patients displays the same trend as what we observed in breast cancer tissues; only some but not all breast cancer samples screened with the aberrant ALOX5 expression.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, the role of ALOX in breast cancer remains much unknown. This study firstly demonstrated that the ALOX5 expression elevated breast cancer tissues compared to control (Figures 1(a) and 1(b) ), which is supported by the report that the mean concentration of serum ALOX5 is significantly higher in breast cancer patients than similar age as the control group [ 17 ]. In addition, the serum level of ALOX5 among individual breast cancer patients displays the same trend as what we observed in breast cancer tissues; only some but not all breast cancer samples screened with the aberrant ALOX5 expression.…”
Section: Discussionsupporting
confidence: 78%
“…Consistently, ALOX5AP which is necessary for the ALOX5 activation via facilitating the docking of AA to ALOX5 has been found to be overexpressed in breast cancer, particularly in aggressive tumors [ 18 ]. In addition, both ALOX5 and ALOX5AP have prognostic and survival significance in breast cancer patients [ 17 , 18 ], suggesting that the elevated level of the expression is functional. This is supported by our observation that the 5-HETE level was significantly increased in breast cancer tissues ( Figure 1(c) ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LOXs and the products of their catalytic activity also have an antiapoptotic effect and promote tumor growth. LOX inhibitors and, to a greater extent, drugs that inhibit the activity of both COX and LOX, have an antitumor effect [20,21]. Baicalein, NDGA and zileuton, the drugs of natural origin used in this work, possess the capacity to inhibit lipoxygenase pathways, which results in their antitumor activity.…”
Section: Discussionmentioning
confidence: 95%